Pengaruh Pendekatan Pembelajaran STEAM terhadap Kemampuan Numerasi Anak Usia 4-5 Tahun - Dita Istiqomah Shaka; Nyimas Atika; Indah Dwi Sartika; Desvi Wahyuni (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2024)
This research aims to determine the effect of the STEAM learning approach on the numeracy abilities of children aged 4-5 years. This type of research is a quantitative experimental research method, Pre-Experimental Design, by trialing the STEAM learning approach in class. This research design is One Group Pre-test – Post-test Design, in the form of a children's worksheet which contains children's understanding of numeracy. The population of this study was 12 children from group A. Data collection techniques include documentation, observation & test techniques. Data analysis techniques in this research use validity tests, reliability, normality, homogeneity, and t-hypothesis tests. Based on the results of research that has been conducted, there is a significant influence on the numeracy abilities of children aged 4-5 years on indicators of counting using numbers, measuring, sorting, and patterns. Apart from that, it is shown by tcount = 26.741 while t table = 2.178. Because count> table (26.741>2.178), the conclusion is that Ha is accepted & H0 is rejected, which means there is a significant influence of implementing the STEAM learning approach on the numeracy abilities of children. This research implies that the STEAM learning approach is very appropriate for children aged 4-5 years because it can teach children to think and problem-solve, including numeracy abilities.